Managing the Invisible : Understanding and Improving Groundwater Governance - Wijnen, Marcus (World Bank, Washington, DC, 2014)
Groundwater is playing an increasingly important role in domestic, industrial and agricultural water supply. With the advent of the tube well and driven by the rapid growth of demand for agricultural and municipal water, annual global groundwater extraction has increased in recent decades from 100 k